Herding with and without Payoff Externalities - An Internet Experiment - Mathias Drehmann; Jörg Oechssler; Andreas Roider (University of Heidelberg, Department of Economics, 2005)
Most real world situations that are susceptible to herding are also characterized by direct payoff externalities. Yet, the bulk of the theoretical and experimental literature on herding has focused on pure informational externalities. In this paper we experi- mentally investigate the effects of several different forms of payoff externalities (e.g., network effects, first-mover advantage, etc.) in a standard information-based herding model. Our results are based on an internet experiment with more than 6000 subjects, including a subsample of 267 consultants from an international consulting firm. We also replicate and review earlier cascade experiments. Finally, we study reputation effects (i.e., the influence of success models) in the context of herding.
Keywords: C92; D8; 330; information cascades; herding; network effects; experiment; internet; Anlageverhalten; Test; Internet; Informationsverhalten; Rationalität; Deutschland; Herdenverhalten